Pengaruh Pengeluaran Pemerintah terhadap Pertumbuhan Ekonomi Aceh - Erni Suryani; Miswar Miswar; Safuridar Safuridar (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the effect of goods and services expenditure and social assistance expenditure on economic growth in Aceh Province. Economic growth is an important indicator of regional development performance and can be influenced by government fiscal policies through regional expenditures. This research employed a quantitative approach using secondary time-series data for the period 2012–2024 obtained from the Central Bureau of Statistics (BPS) of Aceh Province and the Directorate General of Fiscal Balance (DJPK). Multiple linear regression analysis was used to examine the influence of the independent variables on economic growth. The results indicate that goods and services expenditure has a positive and significant effect on economic growth in Aceh Province. Meanwhile, social assistance expenditure has a negative and insignificant effect on economic growth. Simultaneously, both goods and services expenditure and social assistance expenditure affect economic growth. The findings suggest that goods and services expenditure is a more effective component of government spending in stimulating regional economic activities, while social assistance expenditure primarily functions as a social protection instrument. Therefore, local governments should optimize the quality of public spending to support sustainable economic growth.